Strategi Dinas Pariwisata Dalam Mengembangkan Objek Wisata Karst Rammang-Rammang Di Kabupaten Maros - Paradana, Anugerah; Muhammadiyah, Muhammadiyah; Hamrun, Hamrun (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to analyze the development of tourism objects and determine the government's efforts in developing tourism objects in the Rammang-Rammang Forest of Maros Regency. This study used a qualitative method with a descriptive approach to analyze and find out the government's efforts in developing tourism objects. The results showed that the strategy for the development of Kart Rammang-Rammang tourism objects in Maros Regency was based on 4 (four) indicators, namely Human resources could be said to be not optimal yet still require guidance, Many activities that needed the role of the community with the quantity and quality of human resources which was qualified, regarding the distribution of funds that had not been going well because the Government had not managed directly, then information and technology had not been said to be maximized because the Tourism Office and tourism object managers were still lacking in communicating about appropriate promotional media and suitable for the object. Tourism, facilities and infrastructure were still lacking in Kart Rammang-Rammang tourism objects, it was necessary to have participation from related parties and to collaborate with managers and local communities regarding the improvement of facilities and infrastructure.Keywords: Strategy, Development, Tourism Object